Implementasi Pendidikan Karakter Islami dalam Pembelajaran Pendidikan Agama Islam di Sekolah Menengah - Muhammad Syaiful Anwar (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the implementation of Islamic character education in Islamic Religious Education learning at the secondary school level, covering the stages of planning, implementation, evaluation, and the factors influencing its success. This research employed a qualitative approach using a library research method. Data were collected from various sources, including books, scientific journal articles, previous research findings, and other relevant documents, and were analyzed using content analysis through the processes of theme identification, data categorization, interpretation, and synthesis. The findings indicate that the implementation of Islamic character education is integrated into the planning stage by incorporating Islamic character values into learning objectives, teaching materials, instructional methods, learning media, and assessment. During the implementation stage, Islamic character education is carried out through teachers' role modeling (uswah hasanah), habituation of religious practices, integration of character values into learning materials, and the application of instructional strategies that promote cooperation, responsibility, and social awareness.